Pengaruh Motivasi dan Disiplin Terhadap Kinerja Pegawai Dinas Pekerjaan Umum, Tata Ruang dan Pertanahan Kabupaten Solok Selatan - Dewirahmadanirwati Dewirahmadanirwati; Dasril Dasril (Fakultas Sastra Universitas Ekasakti, 2021)
Agencies engaged in public works, infrastructure and housing development for the South Solok Regency area. However, there are still many complaints that are felt by the employees of the Public Works, Spatial Planning and Land Office of South Solok Regency. This study aims to determine the Motivation, Discipline and Employee Performance of the Public Works, Spatial Planning and Land Service Office of South Solok Regency. The samples were determined by using saturated sampling technique, with a total of 64 employees. The data were collected through questionnaires and then analyzed statistically descriptive and Independent-Sample T-Test with the SPSS version 16 program. The results of data analysis showed that motivation and discipline had a positive effect on the performance of the employees of the Public Works, Spatial Planning and Land Office of South Solok Regency.